Comparative Study of Intensity of Echo and Source Sound - Adhikari, Shesh Kant; Adhikari, Dipak Raj; Rana, Keshar Singh (Journal of Physical and Life Sciences, 2024)
Echo is the repetition of sound due to reflection. This repetition sound will be distinct from the original sound. This paper attempt to compare the intensity of source sound and intensity of echo sound. In this experiment ten Nepali isolated words are spoken three times by ten males and ten females at same age group 20 to 25 years and the echo sound produces by the reflection of sound from the properly selected hill. This study helps to investigate the nature of absorption coefficient of reflecting surface and surrounding. The recorded echo and source sound digitize and analyze by Praat software at sampling frequency 16KHz. Linear predictive coding (LPC) spectra were obtained for each word and instantaneous values of minimum, maximum and average intensity were measured for echo and source sounds. Threshold value of intensity of sound is zero (0 dB). For male speakers minimum, maximum, average intensity of source sound and echo sound varies from 57.78 to 67.31dB, 63.76 to 83.24 dB, 60.77 to 74.45 dB and 53.62 to 58.33 dB, 56.30 to 66.94dB, 54.96 to 62.64 dB, respectively. In case of female speakers minimum, maximum, average intensity of source sound and echo sound varies from 63.83 to 71.35, 67.62 to 89.39dB, 66.47 to 78.29 dB and 57.80 to 61.60 dB, 60.21 to 70.23dB, 59.01 to 65.92dB, respectively. The ratios of the average intensity of echo to source sound varies from 0.79 to 0.88 for male speakers and 0.80 to 0.89 for female speakers.